2007
DOI: 10.1002/pbc.20861
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hematoma as a complication of intrathecal methotrexate administration

Abstract: Neurotoxicity of methotrexate is a well‐documented issue, but development of an intracerebral hematoma following administration of intrathecal methotrexate is an extremely rare entity. A 6‐year‐old male with the diagnosis of non‐Hodgkin lymphoma was put on a treatment regimen, including intrathecal methotrexate. Six days following the last intrathecal methotrexate administration, the patient developed a deteriorating state of consciousness. There was no history of trauma. Coagulation studies and platelet count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The authors found only five pediatric cases reported in the literature when using the search words "hemorrhage" or "hematoma" and "lumbar puncture" and "pediatric". These cases are summarized in Table 1 [7,9,[13][14][15]. Of these, the one that is most similar to the case reported herein is a 12-year-old boy with ALL and thrombocytopenia (platelet count 42,000/µL) who underwent a diagnostic LP [15].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The authors found only five pediatric cases reported in the literature when using the search words "hemorrhage" or "hematoma" and "lumbar puncture" and "pediatric". These cases are summarized in Table 1 [7,9,[13][14][15]. Of these, the one that is most similar to the case reported herein is a 12-year-old boy with ALL and thrombocytopenia (platelet count 42,000/µL) who underwent a diagnostic LP [15].…”
Section: Discussionmentioning
confidence: 65%
“…The bleeding at the site of the procedure is likely related to direct trauma to the vasculature within and surrounding the epidural space. Boran et al present an elegant discussion regarding the potential pathophysiology responsible for the CNS bleeding that was noted in their patient and ours [13]. With the removal of CSF during LP and the ongoing leak that may occur following the procedure, there may be a decrease in intracranial pressure (ICP), leading to secondary increase in the volume of intracerebral veins.…”
Section: Lp For Fever Evaluationmentioning
confidence: 82%
See 1 more Smart Citation
“…A few cases have been reported in the literature till date [2][3][4]. As the other possible etiologies of ICH like arteriovenous malformation, hypertension, thrombocytopenia, coagulopathy, history of major head trauma or thrombolytic therapy were excluded in the present case, intrathecal methotrexate was considered to be the probable cause in our patients.…”
Section: Discussionmentioning
confidence: 77%
“…A case-report described significant oral mucosal bleeding in a patient on methotrexate and hydroxychloroquine therapy in the absence of thrombocytopenia or coagulopathy [3]. Intracerebral hematoma due to intrathecal administration of methotrexate has been reported with normal platelet counts and coagulation parameters [4]. A study showed a dosedependent inhibition of platelet aggregation post incubation with methotrexate in in vitro tests.…”
Section: To the Editormentioning
confidence: 99%